Evolución del Conocimiento sobre la enfermedad de la diarrea viral bovina y su agente etiológico - Rivera G., Hermelinda (2008)
The bovine viral diarrhea (BVD), an enzootic disease in the world cattle population, has a tremendous economic impact due to its effect on reproductive failure and health of cows. The economic losses observed since its emergence in the ‘40s and the interesting biology of this virus had prompt an intensive research on the epidemiology, physiopathology and molecular biology of the bovine viral diarrhea virus (BVDV) that have contributed to the evolution of the concept of control of the disease. The purpose of this review is to summarize the most important chronologic events of the BVD and the BVDV. It also describes how the actual knowledge of the structure of the virus genome is contributing to the development of biologic products and current diagnostic tests for controlling the disease.